Mouse Parthenogenetic Embryonic Stem Cells with Biparental‐Like Expression of Imprinted Genes Generate Cortical‐Like Neurons That Integrate into the Injured Adult Cerebral Cortex. (10th November 2017) - Varrault, Annie; Eckardt, Sigrid; Girard, Benoît; Le Digarcher, Anne; Sassetti, Isabelle; Meusnier, Céline; Ripoll, Chantal; Badalyan, Armen; Bertaso, Federica; McLaughlin, K. John; Journot, Laurent; Bouschet, Tristan
Abstract: One strategy for stem cell‐based therapy of the cerebral cortex involves the generation and transplantation of functional, histocompatible cortical‐like neurons from embryonic stem cells (ESCs). Diploid parthenogenetic Pg‐ESCs have recently emerged as a promising source of histocompatible ESC derivatives for organ regeneration but their utility for cerebral cortex therapy is unknown. A major concern with Pg‐ESCs is genomic imprinting. In contrast with biparental Bp‐ESCs derived from fertilized oocytes, Pg‐ESCs harbor two maternal genomes but no sperm‐derived genome. Pg‐ESCs are therefore expected to have aberrant expression levels of maternally expressed (MEGs) and paternally expressed (PEGs) imprinted genes. Given the roles of imprinted genes in brain development, tissue homeostasis and cancer, their deregulation in Pg‐ESCs might be incompatible with therapy. Here, we report that, unexpectedly, only one gene out of 7 MEGs and 12 PEGs was differentially expressed between Pg‐ESCs and Bp‐ESCs while 13 were differentially expressed between androgenetic Ag‐ESCs and Bp‐ESCs, indicating that Pg‐ESCs but not Ag‐ESCs, have a Bp‐like imprinting compatible with therapy. In vitro, Pg‐ESCs generated cortical‐like progenitors and electrophysiologically active glutamatergic neurons that maintained the Bp‐like expression levels for most imprinted genes. In vivo, Pg‐ESCs participated to the cortical lineage in fetal chimeras. Finally, transplanted Pg‐ESC derivatives integrated into the injured adult cortex and sent axonal projections in the host brain. In conclusion, mouse Pg‐ESCs generate functional cortical‐like neurons with Bp‐like imprinting and their derivatives properly integrate into both the embryonic cortex and the injured adult cortex. Collectively, our data support the utility of Pg‐ESCs for cortical therapy. Stem Cells 2018;36:192–205 Abstract : Mouse parthenogenetic embryonic stem cells (Pg‐ESCs) with biparental (Bp)‐like expression of imprinted genes generate cortical‐like neurons that integrate into the injured adult cerebral cortex. Parthenogenetic Pg‐ESCs can be more easily selected for histocompatibility than normal Bp‐ESC lines. However, the application of Pg‐ESCs to cortical therapy is unknown and their parental imprinting might be incompatible with therapy. We report that mouse Pg‐ESCs had a Bp‐like expression of imprinted genes (while androgenetic‐ESCs did not) and that they generated cortical‐like progenitors and electrophysiologically active neurons. In vivo, transplanted Pg‐ESC derivatives integrated into the injured adult cortex. Collectively, this supports the utility of Pg‐ESCs for neocortex repair.